2004
DOI: 10.1007/s00270-003-0147-1
|View full text |Cite
|
Sign up to set email alerts
|

Trisacryl Gelatin Microspheres Versus Polyvinyl Alcohol Particles in the Preoperative Embolization of Bone Neoplasms

Abstract: The aim of this study was to compare the efficacy of trisacryl gelatin microspheres versus polyvinyl alcohol particles (PVA) in the preoperative embolization of bone neoplasms, on the basis of intraoperative blood loss quantified by the differences in preoperative and postoperative hematic levels of hemoglobin, hematocrit and erythrocytes count. From January 1997 to December 2002, preoperative embolization of bone tumors (either primary or secondary) was carried out in 49 patients (age range 12/78), 20 of whom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
0
28
1
1
Order By: Relevance
“…Of 11 patients failing to have LC, 8 were within 120 months, indicating that 10-year survival might be a prognostic threshold to forecast the overall LC rate. Of all included patients, 6 were classified as Campanacci Grade II and 3 as Grade III, but no prognostic significance was observed between the two subgroups in our study.Although no significant difference was shown among embolization materials in our research, as previous demonstrated, Gelfoam, polyvinyl alcohol (PVA), and stainless steel coils for most SAE ran the risk of a short occlusive time of tumor-feeding arteries as well as non-target embolization, which could result in the subsequent failure of LC or even the OS 38,40 . Therefore, superabsorbent polymer microsphere (SAP-MS) is recommended for SAE due to its precise and everlasting occlusion with minimum harm to normal tissue.…”
contrasting
confidence: 47%
“…Of 11 patients failing to have LC, 8 were within 120 months, indicating that 10-year survival might be a prognostic threshold to forecast the overall LC rate. Of all included patients, 6 were classified as Campanacci Grade II and 3 as Grade III, but no prognostic significance was observed between the two subgroups in our study.Although no significant difference was shown among embolization materials in our research, as previous demonstrated, Gelfoam, polyvinyl alcohol (PVA), and stainless steel coils for most SAE ran the risk of a short occlusive time of tumor-feeding arteries as well as non-target embolization, which could result in the subsequent failure of LC or even the OS 38,40 . Therefore, superabsorbent polymer microsphere (SAP-MS) is recommended for SAE due to its precise and everlasting occlusion with minimum harm to normal tissue.…”
contrasting
confidence: 47%
“…[4,7,14] Many studies compared the performances of spherical and nonspherical particles in embolization procedures, proving the much better efficacy of embolization procedures carried out with spherical particles. [13,15,16] In order to overcome some of the undesirable characteristics of available embolization products, a suspension polymerization process was developed to allow for production of spherical core/shell PVAc/PVA particles for vascular embolization. [1,17,18] The core/shell structure of the final polymer beads leads to lower rates of water absorption (when compared to particles constituted entirely by PVA), resulting in improved volume stability of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy is implemented rarely and only to control pain intensity in patients with bone metastases. Embolization of bone metastases performed for similar reasons as in radiotherapy have been reported [1,2]. Systemic treatment is implemented in patients with generalized disease.…”
mentioning
confidence: 96%